IL-33 restricts tumor growth and inhibits pulmonary metastasis in melanoma-bearing mice through eosinophils. (3rd June 2017) - Lucarini, Valeria; Ziccheddu, Giovanna; Macchia, Iole; La Sorsa, Valentina; Peschiaroli, Francesca; Buccione, Carla; Sistigu, Antonella; Sanchez, Massimo; Andreone, Sara; D'Urso, Maria Teresa; Spada, Massimo; Macchia, Daniele; et al.
ABSTRACT: The alarmin IL-33 is an IL-1 family member that stimulates pleiotropic immune reactions depending on the target tissue and microenvironmental factors. In this study, we have investigated the role of IL-33/ST2 axis in antitumor response to melanoma. Injection of IL-33 in mice-bearing subcutaneous B16.F10 melanoma resulted in significant tumor growth delay. This effect was associated with intratumoral accumulation of CD8 + T cells and eosinophils, decrease of immunosuppressive myeloid cells, and a mixed Th1/Th2 cytokine expression pattern with local and systemic activation of CD8 + T and NK cells. Moreover, intranasal administration of IL-33 determined ST2-dependent eosinophil recruitment in the lung that prevented the onset of pulmonary metastasis after intravenous injection of melanoma cells. Accordingly, ST2-deficient mice developed pulmonary metastasis at higher extent than wild-type counterparts, associated with lower eosinophil frequencies in the lung. Of note, depletion of eosinophils by in vivo treatment with anti-Siglec-F antibody abolished the ability of IL-33 to both restrict primary tumor growth and metastasis formation. Finally, we show that IL-33 is able to activate eosinophils resulting in efficient killing of target melanoma cells, suggesting a direct antitumor activity of eosinophils following IL-33 treatment. Our results advocate for an eosinophil-mediated antitumoral function of IL-33 against melanoma, thus opening perspectives for novel cancer immunotherapy strategies.